Identifying Habitats of Conservation Priority in the São Vicente Submarine Canyon in Southwestern Portugal - Nestorowicz, Iga-Maria; Oliveira, Frederico; Monteiro, Pedro; Bentes, Luís; Henriques, Nuno Sales; Aguilar, Ricardo; Horta e Costa, Barbara; Gonçalves, Jorge M. S. (Frontiers in Marine Science, 2021)
Identifying vulnerable marine habitats is fundamental to promote evidence-based management and a sustainable use of our oceans. Although progress in the mapping of marine benthic habitats has been made, complex ecosystems such as submarine canyons remain largely unexplored, hampering evidence-based management from taking place in these ubiquitous features worldwide. Data from a remotely operated vehicle (ROV) survey in the upper São Vicente Submarine Canyon in southwestern Portugal from 2011, was analysed to carry out a comprehensive assessment of megabenthic habitats, particularly those of conservation concern occuring between 90 and 560 m. Underwater videos from three exploratory dives, covering a total of 8.8 kilometers, were analyzed through multivariate and visual assessments, and the identified habitats were assessed against a set of criteria derived from current definitions of priority habitats. Thirteen potential priority habitats were characterized, out of which four distinct “coral gardens” and one “deep-sea sponge aggregation” are aligned with OSPAR definitions of priority habitats, and one corresponds to the habitat of a strictly protected sea urchin listed in the Habitats Directive. Three circalittoral sponge aggregations were also suggested based on the abundance of indicator species. The specific composition and diversity of priority habitats as described here, has not yet been described in any other canyon in the NE Atlantic region. Depth was revealed to be particularly important for the distribution of habitats, followed by relief and substratum. The approach presented in this study contributes to improve the understanding about submarine canyons, which is paramount to implement knowledge-based protection measures. Furthermore, it can be used to support future mapping efforts of deep-sea environments such as submarine canyons.